Determining the optimal pancreatic decellularization protocol, taking into account tissue morphological features - A. S. Ponomareva; N. V. Baranova; L. A. Kirsanova; G. N. Bubentsova; E. A. Nemets; I. A. Miloserdov; V. I. Sevastianov (Вестник трансплантологии и искусственных органов)
Introduction. Developing a tissue-engineered pancreatic construct (TEPC) involves a search for matrices/scaffolds capable of mimicking the structure and composition of the natural extracellular matrix (ECM), which is an important component of the tissue microenvironment. A cell-free, tissue-specific matrix obtained from pancreas decellularization seems to be the most suitable for creation of a TEPC. The choice of pancreatic tissue decellularization protocol should take into account the morphological characteristics of the original pancreas. Preservation of the architectonics and composition of the native tissue in the decellularized pancreas matrix (DPM), and the presence of native ECM components allow for creation of conditions for prolonged vital activity of functionally active islet (insulin-producing) cells when creating TEPC.Objective: to determine the optimal parameters for decellularization of deceased donor pancreas with fibrosis, lipomatosis, and without pronounced signs of fibrosis and lipomatosis.Materials and methods. We used the caudal part of the pancreas obtained after multiorgan procurement from deceased donors, which was unsuitable for transplantation. Tissue-specific matrix was obtained by a combination of physical and chemical methods of pancreatic decellularization. A freeze-thaw cycle protocol and two protocols using osmotic shock were used. Samples of initial pancreatic tissue and decellularized fragments were subjected to histological analysis.Results. It was shown that a physico-chemical method with freeze-thaw cycles is suitable for effective pancreatic decellularization in severe lipomatosis; a physico-chemical method using osmotic shock, but different protocol variants, is suitable for pancreas with diffuse fibrosis and for pancreas without pronounced signs of fibrosis and lipomatosis.Conclusion. For complete human pancreatic decellularization, the protocol should be correlated with histological features of the original tissue.